PENGARUH PEMBERIAN HORMON METHYLTESTOSTERONE PADA LARVA IKAN GUPPY (Poecilia reticulata) TERHADAP PERUBAHAN JENIS KELAMIN - Huwoyon, Gleni Hasan; -, Rustidja -; Gustiano, Rudhy - (ZOO INDONESIA, 2008)
Huwoyon, G.H., Rustidja & R. Gustiano. 2008. Effect of methyltestosterone hormoneon sex reversal of Guppy (Poecillia reticulate) larvae fish. Zoo Indonesia 17(2): 49-54. Male ornamental fish is more exotic than female one. The objective of study wasto increase the percentage of male guppy fish (Poecillia reticulate) usingmethyltestosterone hormone at the larvae stage. Control (A = 0 ppm) and four differentdosages of methyltestosterone hormone (B = 5 ppm, C = 10 ppm, D = 15 ppm & E =20 ppm) were used as treatments with three replications. The results showed the besttreatment to produce the highest percentage (58.41%) of male guppy fish was at 10ppm dosage (p<0.01). However, the dosages hormone treatments given in this studywere not significantly different on intersexes production, survival rate and specificgrowth rate (p>0.05).